Enhancing the fan experience at live sporting events : the case of stadium wi-fi - Levallet, Nadège (SAGE Business Cases., 2019)
While live sport event attendance remains a pervasive and progressing issue for university athletic programs, athletic directors should consider strategies to boost perceptions of stadium innovativeness. Professional sport leagues have pursued the adoption of Wi-Fi capabilities much more aggressively than their collegiate sport counterparts. This case introduces the Wi-Fi adoption issue for collegiate sport including a conversation surrounding the foundational technical aspects of Wi-Fi and cellular data for sport venues, the current status of Wi-Fi for collegiate athletics in comparison with professional leagues, and the benefits and drawbacks of Wi-Fi adoption. Case participants are asked to evaluate the merits of Wi-Fi adoption for a "Power Five" institution from the position of the athletic director. Participants will address adopting functional technology for the rise in college esports, Wi-Fi inclusion for indoor and outdoor venues, and comparative analyses among connected and disconnected stadiums.